A Facile Stereoselective Domino Approach for the Construction of Novel Bis(spiropiperidone)–Tetrahydrothiophene Hybrid Heterocycles - Bharkavi, Chelliah; Kumar, Sundaravel Vivek; Perumal, Subbu (Synlett, 2015)
A library of novel bis-spiropiperidone–tetrahydrothiophene hybrid heterocycles have been synthesized via pseudo-three-component domino reaction of (3E,5E)-3,5-bis(arylidene)-1-methyl/benzyl piperidin-4-ones and 1,4-dithiane-2,5-diol in the presence of triethylamine. This transformation presumably proceeds via two annulations each involving the generation of 2-mercaptoacetaldehyde from 1,4-dithiane-2,5-diol–Michael addition–intramolecular aldol sequence which result in the creation of four new bonds in a one-pot operation. The advantages of this protocol are high atom economy, high stereoselectivity, short reaction time, and operational simplicity.
Keywords: domino reactions; stereoselectivity; (3E,5E)-3,5-bis(arylidene)-1-methyl/benzylpiperidin-4-ones; 1,4-dithiane-2,5-diol; bis(spiropiperidone)–tetrahydrothiophene hybrids